Vendor-based restrictions on pesticide sales to prevent pesticide self-poisoning - a pilot study - Weerasinghe, M; Konradsen, F; Eddleston, M; Pearson, M; Jayamme, S; Gunnell, D; Hawton, K; Agampodi, S (BioMed Central, 2018)
Background: In South Asia, up to 20% of people ingesting pesticides for self-poisoning purchase the pesticide from a shop with the sole intention of self-harm. Individuals who are intoxicated with alcohol and/or non-farmers represent 72% of such high-risk individuals. We aimed to test the feasibility and acceptability of vendor-based restrictions on pesticide sales for such high-risk individuals. Methods: We conducted a pilot study in 14 (rural = 7, urban = 7) pesticide shops in Anuradhapura District of Sri Lanka. A two-hour training program was delivered to 28 pesticide vendors; the aim of the training was to help vendors recognize and respond to customers at high risk of pesticide self-poisoning. Knowledge and attitudes of vendors towards preventing access to pesticides for self-poisoning at baseline and in a three month follow-up was evaluated by questionnaire. Vendors were interviewed to explore the practice skills taught in the training and their assessment of the program. Results: The scores of knowledge and attitudes of the vendors significantly increased by 23% (95% CI 15%–32%, p < 0.001) and by 16% (95% CI 9%–23%, p < 0.001) respectively in the follow-up. Fifteen (60%) vendors reported refusing sell pesticides to a high-risk person (non-farmer or intoxicated person) in the follow-up compared to three (12%) at baseline. Vendors reported that they were aware from community feedback that they had prevented at least seven suicide attempts. On four identified occasions, vendors in urban shops had been unable to recognize the self-harming intention of customers who then ingested the pesticide. Only 2 (8%) vendors were dissatisfied with the training and 23 (92%) said they would recommend it to other vendors. Conclusions: Our study suggests that vendor-based sales restriction in regions with high rates of self-poisoning has the potential to reduce access to pesticides for self-poisoning. A large-scale study of the effectiveness and sustainability of this approach is needed.